SWIM TRAINING REVERSES SOME EFFECTS OF NANDROLONE DECANOATE IN WISTAR RATS - Nascimento,Lilian Cristina Gomes do (2021)
ABSTRACT Introduction: The indiscriminate use of androgenic steroids may have deleterious effects on human tissue. Objectives: Evaluate the effects of chronic administration of the steroid nandrolone decanoate (DECA) on autonomic cardiovascular modulation, kidney morphometry and the association between these variables in Wistar rats subjected to physical training with swimming. Methods: Thirty-two male Wistar rats aged 20 weeks were distributed among four experimental groups according to the training received: sedentary control (SC), sedentary treated with DECA (SD), trained control (TC) and trained treated with DECA (TD). The hemodynamic parameters, including blood pressure and variations in systolic blood pressure (SBPV) and diastolic blood pressure (DBPV), and kidney morphometry were evaluated. The level of significance adopted was 5%. Results: The SD group had higher baseline SBP and DBP values when compared to the SC, TC and TD groups, which were similar to each other. The rats in the SD group had higher systolic blood pressure (SBPV) and diastolic blood pressure (DBPV) variation values and higher absolute and normalized values in the LF band of the DBPV when compared to the animals in the SC, TC and TD groups. The animals in the SD group had a significantly higher rate of kidney fibrosis compared to the SC, TC and TD groups. There were no significant differences between the sympathetic modulation of SBPV through the LF component and kidney fibrosis. Conclusions: Physical training with swimming was effective in preventing the increase in blood pressure levels and lowering the occurrence of kidney fibrosis in animals treated with anabolic steroids. Level of Evidence IV; Series of cases .